2022
DOI: 10.1038/s41467-022-31186-7
|View full text |Cite
|
Sign up to set email alerts
|

Organic donor-acceptor heterojunctions for high performance circularly polarized light detection

Abstract: Development of highly efficient and stable lateral organic circularly polarized light photodetector is a fundamental prerequisite for realization of circularly polarized light integrated applications. However, chiral semiconductors with helical structure are usually found with intrinsically low field-effect mobilities, which becomes a bottleneck for high-performance and multi-wavelength circularly polarized light detection. To address this problem, here we demonstrate a novel strategy to fabricate multi-wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…Thus, achieving switchable detection of L-CPL and R-CPL makes it possible to integrate devices with greater response to both left- and right-handed CPL on a wafer. This outcome is an important contribution to the miniaturization and integration of the CPL-based photodetectors. , Besides, the reported CPL detectors mainly use a sole chiral semiconductor ( S or R ) as the response layer for CPL detection, rendering hence the switchable detection of left- and right-handed CPL challenging. We have to underline that to achieve switchable detection of both L-CPL and R-CPL, the chirality of the CPL-sensitive layer should be tunable.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, achieving switchable detection of L-CPL and R-CPL makes it possible to integrate devices with greater response to both left- and right-handed CPL on a wafer. This outcome is an important contribution to the miniaturization and integration of the CPL-based photodetectors. , Besides, the reported CPL detectors mainly use a sole chiral semiconductor ( S or R ) as the response layer for CPL detection, rendering hence the switchable detection of left- and right-handed CPL challenging. We have to underline that to achieve switchable detection of both L-CPL and R-CPL, the chirality of the CPL-sensitive layer should be tunable.…”
Section: Resultsmentioning
confidence: 99%
“…Organic photodiode is also a two‐terminal device [ 26,90‐92 ] (Figure 3b). It has two operating modes, photoconductive (PC) mode and photovoltaic (PV) mode.…”
Section: Panchromatic Nir Organic Photodetectorsmentioning
confidence: 99%
“…[ 28–32 ] Yet, perhaps counterintuitively, opposite signs for g and g abs were found for some materials. [ 33–36 ] It was also found that g can change sign depending on the thickness of the active layer. [ 33 ]…”
Section: Introductionmentioning
confidence: 99%